2015
DOI: 10.3856/vol43-issue2-fulltext-15
|View full text |Cite
|
Sign up to set email alerts
|

Caligus rogercresseyi: posible vector en la transmision horizontal del virus de la anemia infecciosa del salmon (ISAv)

Abstract: RESUMEN.Chile el año 2007 se convirtió en el segundo país productor de salmónidos a nivel mundial. Al año siguiente la industria salmonera nacional comenzó a experimentar una severa crisis sanitaria producida por el virus causante de la anemia infecciosa del salmón. Este virus se presentó por primera vez en Noruega (1984), luego en Canadá, Escocia, Islas Faroe, Estados Unidos y Chile (2007). La anemia infecciosa del salmón (ISA), es una enfermedad altamente contagiosa entre los peces, producida por un virus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Work by Pino-Marambio et al and Mordue and Birkett [13, 14] has shown that adults and pre-adults will re-assort themselves on fish depending on the availability of potential mates with males being far more motile than females in this regard. Some work has been done looking at sea lice as vectors of disease including infectious haematopoetic necrosis virus (IHNv),[8], infectious salmon anemia virus (ISAv, [15]) and furunculosis [16]. These studies have concentrated on detecting the presence of the pathogen on or in the adult sea louse rather than a full transmission study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Pino-Marambio et al and Mordue and Birkett [13, 14] has shown that adults and pre-adults will re-assort themselves on fish depending on the availability of potential mates with males being far more motile than females in this regard. Some work has been done looking at sea lice as vectors of disease including infectious haematopoetic necrosis virus (IHNv),[8], infectious salmon anemia virus (ISAv, [15]) and furunculosis [16]. These studies have concentrated on detecting the presence of the pathogen on or in the adult sea louse rather than a full transmission study.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have concentrated on detecting the presence of the pathogen on or in the adult sea louse rather than a full transmission study. [15,16] The major pathological effects result from the mobile stages, which can consume large amounts of epithelial tissue forming large lesions through which secondary infection can gain access. It is feasible that if the motile stages feed on a fish that is already infected with a pathogen then it acts as a vector or fomite for that pathogen if the lice leave the infected host and settle on a naïve fish.…”
Section: Introductionmentioning
confidence: 99%
“…Caligus spp. can be vectors and act in the horizontal transmission of the infectious salmon anemia virus among fish (Oelckers et al 2015, Elgendy et al 2015, Brookson et al 2020. Infestations by these ectoparasites can influence the fish recruitment and population growth through direct mortality and potentially through parasite-mediated sublethal effects on host behavior, growth, predation risk, and reproductive success (Brookson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Caligus spp. was reported to cause skin lesions in fish which predisposes fish to secondary infection and later severe issues such as bacterial kidney disease, infectious pancreatic necrosis and rickettsial septicaemia (Bondad‐Reantaso et al, ; Johnson et al, ; Oelckers et al, ). Additionally, the genus Caligus is frequently encountered parasitizing on marine fish parasites (Johnson et al, ; Rohde, ).…”
Section: Introductionmentioning
confidence: 99%